Electric field emissions of FPGA chip based on gigahertz transverse electromagnetic cell modeling and measurements - Chua, King Lee (2016)
Modem integrated circuits (!Cs) are significant sources of undesired electromagnetic wave. Therefore, characterization of chip-level emission is essential to comply with EMC tests at the product level. A Gigahertz Transverse Electromagnetic (GTEM) cell is a common test instrument used to measure IC radiated emission and the test cost is relatively low. Regular IC radiated emission measurements using GTEM tend to neglect some significant emission sources. Thus, this research proposed an alternative methodology to perform field measurement of the IC inside the GTEM cell in order to optimize the field measurements. This research study also attempted analysis of the overall GTEM cell performance using transmission line theory. An FPGA chip was adopted as the IC under test because of its flexibility in configuration to any digital circuit. The investigations discovered that the impact of the FPGA board supporting components and interconnection cables can be significantly reduced with appropriate shielding and grounding. The electric field predict a far distance from the FPGA chip was carried out based on the dipole moment technique. In particular, the dipole moment model emphasizing the tiny horizontal and vertical radiation elements inside the FPGA chip as Hertzian antenna and small current loop. Equations to predict the horizontal and vertical electric field were developed based on Hertzian antenna and small current loop which relate the tiny radiation sources to electric and magnetic dipole moments. The prediction was validated with 3-meter field measurements in a semi-anechoic chamber. On top of that, a spiral-like pattern was developed to obtain a correction factor for further improvement of the correlation between prediction and SAC measurement. The results revealed that the correction factor effectively reduced the gap between the prediction and measurement fields and boosted the correlation coefficient by 44%. The difference of peak values also has limited to less than 1 OdB after correction. These results suggest a promising finding for a future EMI test of ICs with a cheaper GTEM cell.